2014
DOI: 10.1161/strokeaha.113.003133
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Intracranial Aneurysms With MR Angiography

Abstract: Background and Purpose-The aim of this study was to evaluate the sensitivity and specificity of MR angiography (MRA) in the diagnosis of ruptured and unruptured intracranial aneurysms. Methods-A systematic search was performed on 4 electronic databases on relevant articles that were published from January 1998 to October 2013. Inclusion criteria were met by 12 studies that compared MRA with digital subtraction angiography as reference standard. Two independent reviewers evaluated the methodological quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(107 citation statements)
references
References 30 publications
0
98
0
9
Order By: Relevance
“…4). A meta-analysis of MRA studies for evaluating aneurysms demonstrated that contrast-enhanced MRA (CE-MRA) and TOF had similar sensitivity for the detection of aneurysms [27]. CE-MRA, however, was found to be superior to TOF sequences because of its ability to eliminate flow-related artifacts and spin saturation [28].…”
Section: Mri/mra Aneurysm Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). A meta-analysis of MRA studies for evaluating aneurysms demonstrated that contrast-enhanced MRA (CE-MRA) and TOF had similar sensitivity for the detection of aneurysms [27]. CE-MRA, however, was found to be superior to TOF sequences because of its ability to eliminate flow-related artifacts and spin saturation [28].…”
Section: Mri/mra Aneurysm Detectionmentioning
confidence: 99%
“…With current sequences, the spatial resolution at 1.5 T is often as low as 1 mm [31], whereas at 3 T the spatial resolution can be as low as 0.6-0.7 mm while preserving the signal-to-noise ratio [32]. Radiologists also unanimously report significantly better visualization of aneurysms at 3 T. A meta-analysis by Sailer et al [27] that evaluated the sensitivity of MRA for detection of cerebral aneurysms found a trend towards significance in better detection of smaller aneurysms on 3 T versus 1.5 T scanners (p = 0.054). This study reported a pooled sensitivity of 1.5 T and 3 T scanners of approximately 95 % for all aneurysms.…”
Section: Mri/mra Aneurysm Detectionmentioning
confidence: 99%
“…Ancak işlemin uzun sürmesi ve artefaktlardan yoğun olarak etkilenmesi tetkikin kullanımını kısıtlamaktadır. Literatürde MRA'nın DSA ile karşılaştırmasında, anevrizma saptamada yüksek değerlik ve doğrulukta olduğunu vurgulayan çalışmalar mevcuttur (6)(7)(8) . BTA'nın DSA'ya göre ucuz, kolay ulaşılabilir, hızlı ve güvenli olması, acil şartlarda kolaylıkla uygulanabilmesi ve özellikle de non-invaziv olması nedeniyle, DSA yerine kullanımı kabul gören ve yaygın kullanılan bir teknik hâline gelmiştir.…”
Section: Discussionunclassified
“…Aneurysms can be easily identified if the examination protocol includes MR angiography. Due to its local resolution, TOF angiography also has high sensitivity for even small aneurysms [38]. However, they can also be distinguished in contrast-enhanced T1w images (• ▶ Fig.…”
Section: Aneurysmsmentioning
confidence: 99%